Traditional Elements in the Iranian Realistic Drama - Farindokht Zahedi (Institut Seni Indonesia Yogyakarta, 2018)
Modern Iranian drama developed in line with a liberal school of thought, bothbefore and after the Constitutional Revolution in 1906. It came during thetransition from a traditional to a new type of society that was able to tolerateand accept the revolution. The arrival of European theatre in 1878, with itsdependence on a written text rather than improvisatory acting, was part of themodernization process in Iran that enjoyed its height in the early years of thetwentieth century. At the same time, traditional theatre was being rediscovered,and playwrights started using some of its forms to develop indigenous modernIranian theatre to meet the standards of the genuine past and dynamic present.Although there was an assimilation of certain secular tendencies, the newlyappearing type of drama satisfied the need for modernity through defendingpolitical and social liberties. The road to transition began in the 1850’s andgained momentum during the 1940’s through the 1970’s, leaving its effects onIranian drama in such a way that its legacy persists to date.Keywords: realistic drama; Iranian drama; Iran Constitutional Revolution